HOLE ANALYSIS OF CARBON FIBER REINFORCED POLYMER (CFRP) LAMINATES STACK DRILLING IN AN AIRCRAFT APPLICATION - MOHD YAZIT, LUKMAN NULHAKIM (2018)
Laminates stack drilling is a cutting process that use drill bit to create hole of circular cross-section on multilayer and high thickness measurement. This experiment is focusing on hole-making drilling process with stack of three laminated Carbon Fiber Reinforced Polymer (CFRP). Research study on the drilling of single laminates have been comprehensively established. However, the research on the drilling of composite laminate stacks is very much limited. Therefore, that is a need to develop cutting procedure to look at the effect of processing parameter on the product defect. The mechanical drilling on laminate stacks composite material is focuses mainly on drill mechanism, cutting parameter, tool types, drill tool geometry and material. Determine of those aspects have correlation with damage extension caused by the drilling operation. There are two category of defects in composite material which are surface defect and subsurface defect. The objective of the project is to develop processing technique together with cutting parameters on the drilling of CFRP laminates stack. Next, to study about image processing algorithm for identifying defects on laminates stack after drilling process and evaluate defected area and circularity of laminates stack drilled hole based on drilling procedure using most ideal method.